CLINICAL EFFECTIVENESS OF DIET THERAPY IN CHRONIC HEPATITIS (Global Conference on Medical and Health Sciences, 2026)
This study provides a comprehensive evaluation of the clinical effectiveness of diet therapy in patients with chronic hepatitis based on contemporary scientific evidence. The findings indicate that dietary interventions are associated with a 20–35% reduction in liver enzymes (ALT, AST), decreased hepatic steatosis, and improvement in fibrosis indices. Caloric restriction of 7–10% contributes to the regression of liver fat accumulation, while low-carbohydrate diets significantly improve insulin resistance. The results demonstrate that diet therapy has not only symptomatic but also pathogenetic significance. Modern approaches highlight that the combination of diet therapy with pharmacological treatment leads to optimal clinical outcomes. Therefore, diet therapy should be considered a primary, modifiable, and cost-effective strategy in the management and prevention of chronic hepatitis.
Keywords: Chronic hepatitis, diet therapy, liver enzymes, ALT, AST, steatosis, fibrosis, insulin resistance, metabolic syndrome, low-carbohydrate diet, Mediterranean diet, prevention.